Rapid and nondestructive characterization of multiple frying sunflower oil blend using fourier transform infrared spectroscopy and chemometrics. Issue 1 (31st December 2022) - Ahmad, Muhammad Haseeb; Saeed, Nimra; Imran, Muhammad; Kamran Khan, Muhammad; Muhammad, Niaz; Sahar, Amna; Khan, Muhammad Imran
ABSTRACT: Safety and quality of the final product depend on the oil quality that is normally used for the frying purpose. In current study, sunflower oil blend with extra virgin olive oil (EVOO) and palm olein was optimized by D-optimal design and the best blend was chosen for multiple frying of frozen potato fries. Ten frying were performed and free fatty acid (FFA), peroxide (PV) and iodine (IV) values including Fourier transform–infrared (FT-IR) spectral signatures were recorded after each frying. The spectral fingerprints were preprocessed with standard normal variate and then principle component analysis was applied, which showed clear differentiation for various frying. Similarly, partial least square regression was used to predict the FFA, PV and IV which showed high coefficient of determination (R 2 ) 0.83, 0.92 and 0.85, respectively. It can be concluded that FT-IR can be used as an innovative tool for rapid and nondestructive evaluation of frying oils.